The Effect Of Teaching Methods (Lecturing, Reading, Cooperative Learning, And Skill Training) And The Level Of Intelligence On The Outcomes Of Learning Arabic In High School/تأثير طرق التعليم (المحاضرة و القراءة و التعليم التعاوني و تدريب المهارة) ومستوى الذّكاء لنتائج تعلم اللغة العربية فى المدرسة العالية - Setawati, Iga (UIN Raden Mas Said Surakarta, 2020)
This study aims to know the Interaction between teaching methodology and intelligence on learning achievement in Arabic at MAPK MAN 1 Surakarta year lesson 2019/2020. This research applied quantitative. Conducted at MAPK MAN 1 Surakarta from January-February 2020. While the sample is class XI PK. The approach used in this study is a quantitative approach using experimental methods. collection techniques using Observation, Test, and Documentation. Analysis techniques using the normality test, homogeneity test, and hypothesis testing. The conclusion of this research is the influence of teaching method (Lecture, Recitation, and Grup in Work, Skill Training) and the level of Intelligence on Arabic learning Achievement in MAPK MAN 1 Surakarta. There were significant differences in Arabic learning using the lecture and recitation methods and students taught using group work methods and skills training. from the calculated r-value greater than r-table, namely rh = 0.49> 0.44 = rt, There was a difference in the learning to students with low IQ or students in 1` lower IQ group. the calculated r-value greater than the table, namely: rh = 0.78> 0.44 = rt, The method of teaching group work and skills training can significantly improve students' learning in the experimental class when compared to the control group. This can be seen from the difference in the average value achieved by the two groups where the experimental group is greater than the control group, namely: 96> 94.